Photodynamic treatment of multidrug-resistant bacterial infection using indium phosphide quantum dots. (11th November 2022) - Lee, Ilsong; Moon, Jieun; Lee, Hoomin; Koh, Sungjun; Kim, Gui-Min; Gauthé, Laure; Stellacci, Francesco; Huh, Yun Suk; Kim, Pilhan; Lee, Doh C.
Abstract : Photodynamic therapy using indium phosphide quantum dots represents an efficient treatment for infections caused by multidrug-resistant bacteria with minimal mammalian cell toxicity. Abstract : Infections caused by multidrug-resistant (MDR) bacteria pose an impending threat to humanity, as the evolution of MDR bacteria outpaces the development of effective antibiotics. In this work, we use indium phosphide (InP) quantum dots (QDs) to treat infections caused by MDR bacteria via photodynamic therapy (PDT), which shows superior bactericidal efficiency over common antibiotics. PDT in the presence of InP QDs results in high-efficiency bactericidal activity towards various bacterial species, including Staphylococcus aureus, Bacillus cereus, Escherichia coli and Pseudomonas aeruginosa . Upon light absorption, InP QDs generate superoxide (O2 ˙ − ), which leads to efficient and selective killing of MDR bacteria while mammalian cells remain intact. The cytotoxicity evaluation reveals that InP QDs are bio- and blood-compatible in a wide therapeutic window. For the in vivo study, we drop a solution of InP QDs at a concentration within the therapeutic window onto MDR S. aureus -infected skin wounds of mice and perform PDT for 15 min. InP QDs show excellent therapeutic and prophylactic efficacy in treating MDR bacterial infection. These findings show that InP QDs have great potential to serve as antibacterial agents for MDR bacterial infection treatment, as an effective and complementary alternative to conventional antibiotics.